Potential and Possibility of Direct Use of Guano as Fertilizer in Indonesia - Suwarno .; Komaruddin Idris (Jurnal Ilmu Tanah dan Lingkungan, 2007)
Guano is a material originally from sea bird or bat excrement. This material is an important source of P fertilizerduring nineteenth century and the early part of twentieth century. The development of artificial fertilizers and the depletion of guano deposits in Peru caused guano negligibled from world fertilizers trading. Recently, guano appeared in fertilizers trading and sciencetific publications again due to the development of organic farming and increasing the price of energy sources for fertilizer manufacture. Based on its origin, guano is classified into sea bird and bat guanos; and based on its composition guano is grouped into nitrogenous dan phosphatic guanos. Moreover, guano deposits are divided into two types: cave guano and insular guano deposits. The main component of guano is N, P, and Ca elements, and the additional elements are K, Mg, and S. Both nitrogenous and phosphatic guanos are important organic fertilizers because the N content of nitrogenous guano and the P content of phosphatic guano are far higher than those of manure, agricultural waste, or muniCipal waste. In Indonesia guano deposits are widely distributed in Sumatera, Java, Kalimantan, Sulawesi, Nusatenggara, and Irian Jaya. The most deposits are cave guano deposits which contain thousands to hundred thousands tons of guano.Consequently, it is highly potential to develop direct use of guano in our country. Futhermore, results of experiments indicated that phosphatic guano has high possibility to be used directly as P fertilizer.